The Frankopans, Counts of Krk and the Reflections of a "1400 style" on a Periphery of the Kingdom - Marković, Predrag (2011)
During the first half of the 15th century, the area of inland Croatia witnessed the construction or reconstruction of numerous fortified cities, churches and monasteries, all due to the intercession of the Counts of Krk from the House of Frankopan. Their intense political and family relations with the most influential ruling and noble families of the time, King Sigismund and the Counts of Celje (Cilli) defined their position in the cultural circles of Central Europe and enabled the House of Frankopan to become the promoters of the most advanced architectural and artistic enterprises of the period. One of such works of art representing direct testimonies of their cultural policy and artistic preferences is certainly Sokolac, a burg in the modern-day town of Brinje, with the two-storey court chapel of the Holy Trinity, erected at the very beginning of the 15th century. In his analysis of the construction features of the burg in Brinje, Zorislav Horvat (1983) identified several crucial elements that link it to Czech military architecture of late 14th century. For the Chapel of the Holy Trinity Count Nikola IV Frankopan hired skilled masters from the court workshop of Wenceslaus IV. One of them surely came from the nearby Carthusian church of the Holy Trinity in Pleterje, since the same stonecutter mark is found on both building sites.
Projekt MZOS
ENG